Methylphenidate affects task-switching and neural signaling in non-human primates. - Rajala, Abigail Z; Populin, Luis C; Jenison, Rick L (Psychopharmacology, 2020)
Rationale: Low doses of psychostimulants such as methylphenidate (MPH), which increase extracellular dopamine and norepinephrine by inhibiting their reuptake, are the most commonly used treatment for attention deficit hyperactivity disorder (ADHD). Therapeutic doses of these drugs may improve focused attention at the expense of hindering other cognitive functions, including the ability to adapt behavior in response to changing circumstances—cognitive flexibility. Cognitive flexibility is thought to depend on proper operation of the prefrontal cortex (PFC) and is also linked to reward processing, which is dopamine-dependent. Additionally, reward outcome signals have been recorded from the PFC. Objectives: This study tested the hypothesis that therapeutic doses of MPH impair cognitive flexibility and that this impairment in performance resulted from interference in reward signals within the PFC. Methods: Four rhesus monkeys were given therapeutically relevant doses of oral MPH (0, 3, and 6 mg/kg) while performing an oculomotor switching task to evaluate its effect on task performance. Single-unit recordings in the PFC of two monkeys were taken before and after MPH administration during task performance. Results: The results show that MPH does hinder switching task performance, an effect that was correlated with a reduction in the amplitude of outcome signals found in the discharges of some neurons in the PFC. Conclusions: Methylphenidate impaired task-switching performance, which can be used as a measure of cognitive flexibility. This detriment may result from degraded outcome signaling within the PFC. This study has implications for the use of MPH in the treatment of ADHD.